Investigation of the Effect of Different Types of Steel Fiber on High Performance Fiber Reinforced Cementitious Composite (HPFRCC) Beams with Different Aspect (a/d) Ratios - da Costa Gaspar, Hugo Aureliano (Universiti Teknologi PETRONAS, 2017)
Conventional concrete is very brittle, thus when subjected to sudden loads it tends to fail. To overcome this flaw and sustainability problems, High Performance Fiber Reinforced Cementitious Composites (HPFRCC) was developed. To further understand this cementitious composite, this research focuses on the study of the influence of different types of steel fiber on the mechanical properties of HPFRCC as well as on their influence on the shear failure mode of steel reinforced HPFRCC beams with different span to aspect (a/d) ratios. From the results obtained, despite both types of steel fibers utilized – straight and hooked – having the same tensile strength, the performance of straight steel fiber is superior to the hooked steel fiber due to its physiognomies, where the compressive, tensile and flexural strength of the cementitious composites is superior by 11%, 46% and 1.83%, respectively. It was also noticed a better defection capability by the straight steel fibers when subjected to shear load. On the other hand, the hooked steel fiber had a better shear load capability by 29%. Moreover, with the increment of the aspect (a/d) ratio of HPFRCC beams from 2 to 3.5, the angle of the failure line of the HPFRCC beams decreases.